Mouthpart morphology and feeding behavior of the invasive kudzu bug, Megacopta cribraria (Hemiptera: Plataspidae). Issue 3 (15th June 2017) - Stubbins, Francesca L.; Mitchell, Paula Levin; Turnbull, Matthew W.; Reay‐Jones, Francis P. F.; Greene, Jeremy K.
Abstract: The invasive kudzu bug, Megacopta cribraria, was first reported in North America in 2009 and has subsequently spread through most of the southeastern United States, causing yield loss in soybean. Since detection in the USA, research has focused mainly on managing this newly established pest, but many important characteristics of the pest's mouthpart morphology and feeding behavior are unknown. Qualitative and quantitative comparisons of nymph and adult mouthparts and sensilla were made through scanning electron microscopy and light microscopy, and feeding behavior was examined using electropenetrography (EPG) and paraffin histology. Morphologies observed were similar to what has previously been reported for other piercing–sucking hemipterans. The relationship between rostrum length and body size (pronotum width and dorsal length) exhibited negative allometry. Rostrum length exhibited an isometric relationship with interocular width. Adult females ( n =9) probed soybean stems 1.3±0.8 times in 9 h, with an average probe time of 2.3±1.3 h. EPG waveforms were characterized and correlated with behavior. Salivary sheaths were shown to terminate in the vascular tissue; four of five sheaths terminated in the phloem. This is the first time that the feeding behavior of a member of the Plataspidae has been recorded using EPG. Results add to our current limited knowledge of plataspid mouthpart morphology and provide a baseline for further research on the feeding behaviors of M. cribraria and other soybean‐feeding hemipterans.